THE INFLUENCE OF DIGITAL TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL PERFORMANCE THROUGH INTELLECTUAL CAPITAL MEDIATION AND INNOVATION FACTORS AT PT .XYZ - Juvika Juvika; Ardi Ardi (Jurnal Ekonomi, 2023)
The current era of digitalization is a very important era because it is still a transition from the previous era. The acceleration of digitalization is supported using information technology, which is increasing very rapidly, one of which is the use of internet media so that the performance of internet providers is important to pay attention to. This study examines the effect of digital transformational leadership on organizational performance through the mediation factor of intellectual capital and innovation in one of the internet providers companies in Indonesia. The analysis technique uses Structural Equational Modeling (SEM) with the Smart-PLS program. The results of the research show that all hypotheses are accepted, and all the characteristics of the influence are positive. Where digital transformational leadership has a positive influence on organizational performance, intellectual capital, and innovation. Likewise, intellectual capital and innovation have a positive influence on organizational performance.